2000
DOI: 10.3758/bf03213803
|View full text |Cite
|
Sign up to set email alerts
|

The influence of global discourse on lexical ambiguity resolution

Abstract: The influence of global discourse on the resolution of lexical ambiguity was examined in a series of naming experiments. Two-sentence passages were constructed to bias either the dominant or the subordinate meaning of a homonym that was embedded in a locally ambiguous sentence. The results provided evidence for the immediate (O-msec interstimulus interval) resolution of lexical ambiguity and were subsequently replicated in Experiment 2, in which an 80-msec stimulus onset asynchrony exposure duration was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 63 publications
2
42
0
2
Order By: Relevance
“…Manipulated items taken from Vu et al 1998) In addition to showing that contextually appropriate meanings can be made available by the central, predictive mechanism, irrespective of and even before lexical processes are invited, we further demonstrate that coded but contextually inappropriate meanings are also made available swiftly; they get activated automatically by the modular mechanism, irrespective of contextual fit (Peleg et al 2001, Ex. 2).…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…Manipulated items taken from Vu et al 1998) In addition to showing that contextually appropriate meanings can be made available by the central, predictive mechanism, irrespective of and even before lexical processes are invited, we further demonstrate that coded but contextually inappropriate meanings are also made available swiftly; they get activated automatically by the modular mechanism, irrespective of contextual fit (Peleg et al 2001, Ex. 2).…”
Section: Introductionsupporting
confidence: 51%
“…Recent findings seem to corroborate this model. They show that, in a highly specific context such as (1), only compatible meanings were made available (Vu and Paul 1998;Vu et al 2000; for an extensive review of the literature on the direct/selective access model, see Giora 2003;Gorfein 1989;Simpson 1994;Small et al 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Simpson and Krueger (1991) have demonstrated that a strongly biased context could lead to the activation of only the contextually appropriate meaning of an ambiguous word. Finally, Kellas and colleagues (e.g., Martin, Vu, Kellas, & Metcalf, 1999;Vu, Kellas, Metcalf, & Herman, 2000;Vu, Kellas, & Paul, 1998) have established that ambiguity resolution depends on a complex interaction among meaning frequency, context type, and strength of the biased context. Critically, it was found that although meaning frequency does play an important role, its effect can be eliminated, depending on context strength.…”
Section: Situation-based Knowledge and The Resolution Of Lexical Ambimentioning
confidence: 99%
“…Evidence from lexical decision, naming, and self-paced reading studies has demonstrated that in strongly biasing contexts, reaction times to contextually appropriate items are facilitated but reaction times to contextually inappropriate meanings are not (Kellas, Martin, Yehling, Herman, & Vu, 1995;Martin, Vu, Kellas, & Metcalf, 1999;Simpson, 1981;Vu, Kellas, Metcalf, & Herman, 2000;Vu, Kellas, & Paul, 1998;Vu, Kellas, Petersen, & Metcalf, 2003).…”
mentioning
confidence: 99%